PANDANGAN UNDANG-UNDANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM TERHADAP NIKAH MUTâAH - Rianto, Agus (PARENTAL, 2013)
In Act No. 1 of 1974 on Marriage is stated, that "marriage is a bond between the inner and outer man with one woman as husband and wife with the intention of forming families (households) are happy and eternal deity by The Almighty." Therefore, the bond of marriage are the inner and outer tie for ever for the couple. Similarly in Islamic Law Compilation desired, that a marriage is a strong bond to form a happy family and unseen. In fact in society there are still people who do Mutah marriage or intended marriage contract is only for a short while only, because the Mutah marriage is no intention of a pair of men and women to get married for ever. They just got married by a certain time only contracts. Of course such marriages violated the Islamic law that already prohibits Mutah marriage and also violate the purpose and nature of the actual marriage under the Act No. 1 of 1974 on Marriage and the Compilation of Islamic Law. Mutah marriage can be detrimental to either party who lodged the marriage, either the wife, husband or child, when the marriage contract was born a child, because Mutah marriage is a marriage that is not officially in recordingÂ  marriage and violate any law.